Realists Divided by Realism? Wright on Triune Christianity. - Morgan, Jamie (Journal of Critical Realism, 2015)
In this review article various aspects of Andrew Wright's Christianity and Critical Realism are explored . Wright claims that Trinitarian theology is essentially realist in its form and that realism can be used to defend or justify Trinitarian Christianity. The nature of the specific case brings to the fore a number of issues regarding the nature of reasoning and judgemental rationality for realists.